The Theoretical and Experimental Research on Performance of Bubble Pump with Different Lift Height - Zhao Rongxiang; Liu Daoping; Liang Yu; Chen Yongjun; Lu Yinzhe (Zhileng xuebao, 2014)
In order to grasp the influence parameters of bubble pump performance more accurately and improve the performance of Einstein refrigeration, the theoretical model and experiment on bubble pump were carried out with water as the working fluid at atmospheric pressure by using different lift height under the same immersion ratio. According to the theoretical and experimental results, it is found that under the condition of the other factors unchanged, the theoretical and experimental results have the same trend; the amount of the lifted liquid is inversely proportional to the lift height, the lifting capacity difference can reach to 0.82g/s; the lift height is proportional to the lifting efficiency, and the maximum lifting efficiency difference can reach to 10.16%, which has a important effect on the whole refrigeration system.